A Review of Hypernuclear Physics: Review: Hypernuclear - Shah Bukhari, Masroor Hussain (Biological Sciences - PJSIR, 2010)
A concise overview of fundamental S hypernuclei physics and the mechanisms of hypernucleus for- mation and interactions are presented. S-L interaction and strong force-mediated hyperon-nucleon interaction are introduced to give an epigrammatic background and current perspective of the subject. A model phenomeno- logical elementary Sigma-Nucleus (S-N) potential has been constructed and reported here as an instance of SN interaction. The potential incorporates both spin and isospin dependence and may be useful in calculating Hamil- tonians, cross sections and decay widths in S hypernuclear reactions.